TRADITIONAL KNOWLEDGE AND RESTORATION OF PERMANENT PRESERVATION AREA IN RONDONIA. BRAZIL (FLOVET - Boletim do Grupo de Pesquisa da Flora, Vegetação e Etnobotânica, 2020)
Abstract: Restorations of anthropogenically degraded ecosystems present a relative demand for information that influences the success of the project. Environmental analysis, with the interface of ethnobotany and the management of the rural producer with the plants that make up these areas can make the experiments successful. We aimed verify the environmental perception and ethnobotany in the area of permanent preservation (PPA) restored in the Western Amazon. Data were collected through semi-structured and open interviews, direct observation, life history and walks-in-the-woods and participant observations. The restoration takes place nine years ago and was implemented to comply with environmental legislation. Currently the revegetation area serves as an ecological corridor, animal shelter and protection of local water resources, and has been evaluated positively given the environmental importance for the region. The most represented botanical families were Fabaceae and Meliaceae their products are considered sources of food and medicines. The revegetation in the area provides shading, which favors the volume of the water course and also influencing the local microclimate. Keywords: Restoration, Traditional knowledge, Ethnobotany